Les enseignants de lycée à l’épreuve de l’éducation à l’orientation - Chloé Pannier; Christophe Michaut (Éducation et Socialisation)
In France, the "Orientation and Student Success" law of March 8, 2018, created the Parcoursup platform and strengthened the role of high school teachers in guiding young people in their orientation. Untrained for this, the latter nevertheless have to deal with this mission and the new features induced by the platform, which is the subject of strong criticism due in particular to the inequalities it generates. The potential adjustments required to cope with this challenge the professional identity of high school teachers. The research focuses on the way the latter accept or resist the reform through the prism of their reception and implementation. 23 high schools teachers were interviewed in the framework of comprehensive semi-directive interviews. The results highlight a lack of training and skills in this area among the respondents. The latter felt illegitimate and remained uncertain about the effects that their support could have on the students' progress. Despite their convergent perceptions of orientation, they reinterpret and adjust to this mission according to their seniority, their discipline and the context of their school. They have to do a "makeshift job" in order to adapt to the injunctions as best they can.